Telomerase Inhibition in the Treatment of Leukemia: A Comprehensive Review - Elżbieta Bartoszewska; Klaudia Molik; Marta Woźniak; Anna Choromańska (MDPI AG, 2024)
Leukemia, characterized by the uncontrolled proliferation and differentiation blockage of myeloid or lymphoid precursor cells, presents significant therapeutic challenges despite current treatment modalities like chemotherapy and stem cell transplantation. Pursuing novel therapeutic strategies that selectively target leukemic cells is critical for improving patient outcomes. Natural products offer a promising avenue for developing effective chemotherapy and preventive measures against leukemia, providing a rich source of biologically active compounds. Telomerase, a key enzyme involved in chromosome stabilization and mainly active in cancer cells, presents an attractive target for intervention. In this review article, we focus on the anti-leukemic potential of natural substances, emphasizing vitamins (such as A, D, and E) and polyphenols (including curcumin and indole-3-carbinol), which, in combination with telomerase inhibition, demonstrate reduced cytotoxicity compared to conventional chemotherapies. We discuss the role of human telomerase reverse transcriptase (hTERT), particularly its mRNA expression, as a potential therapeutic target, highlighting the promise of natural compounds in leukemia treatment and prevention.